Perancangan Digital Art dan Lighting Surabaya Night Zoo di Kebun Binatang Surabaya - Jessica Tjiptawan; Purnama Esa Dora Tedjokoesoemo; Muhammad Taufan Rizqy (Intra, 2019)
Surabaya Zoo or often referred as KBS is a nature-themed recreation place with various types of animals in it. In 2019, KBS plans to establish a new recreation area at night, namely Surabaya Night Zoo. As an effort to increase public interest in Surabaya Night Zoo development plan, innovation is needed in its design. The use of digital art installations and lighting showed in public places is still considered as new thing in Indonesia that will make Surabaya Night Zoo different from the other night zoos. The design focuses on the digital technology, the position and color of the lighting applied and the content that will be displayed. All digital technology and lighting are adjusted to zoo animal conditions and are based on literature and research. Brainstorming is also been done with the purpose of optimizing design results from all design aspects.